Analysis of Public Transport Rates Based on Vehicle Operational Costs and Consumer Willingness to Pay (WTP) - Ratna Purwaningsih, Handy Nugroho (USIM, THAMKAM, KHON KAEN, UMY, 2016)
Determination of public transport fares require the right policy to bridge the interests of passengers as consumers and employers as providers of public transport services. Many factors affect the transport tariffs, such as public purchasing power, the cost of maintenance, spare parts price, fuel prices, facilities and infrastructure, etc. This study aim to define a long-distance bus fares based on vehicle operational costs and willingness to pay of consumers by taking a case study on Solo - Jabodetabek bus route for executive class. The method for determining the operational costs of transport services is to determine the vehicle operational cost (VOC) value which consist of direct costs and indirect costs of transportation services. The ability of passengers to pay measured by the method WTP (willingness to pay). These two indicators became a trade-off to determine the tariff by considering a targeted rate of profit by a transportation services company. The results showed that the VOC value and the WTP value did not have much difference. Then, profits cannot be targeted too large. The values obtained using Load factor of 75 % of the number of bus seats. The study also perform simulations to determine the revenue of transportation services at different levels of load factor to determine the breakeven point per vehicle per trip. Results of the research is expected to provide an overview for the company in determining the ticket fare per passenger.